Value of pharmacy services for common illness symptoms covered by universal coverage at drugstore compared to outpatient services at a hospital in Thailand - Parun Rutjanathamrong; Tuangrat Phodha; Thanawat Wongphan; Sirikorn Sujinnaprum; Noppakun Thammatacharee (Taylor & Francis Group, 2024)
Background Drug stores is an option that people can receive health care services for their common illnesses. This is the first study aims to estimate cost savings for 16 common illness symptoms to the Thailand's health system.Method This study gathered retrospective secondary data from several studies and surveyed the median cost of medicines. Cost savings of care provided by pharmacists at drug stores in comparison to out-patient department (OPD) services at hospitals were quantified using cost of illness approach.Results The average number of hospital visits for treatment for 16 common illness symptoms was 2,356 visits per month. The estimation of the cost savings per visit from three perspectives, including government, patient, and societal, at tertiary care hospitals were 12.7-19.4, 12.7-25.6, and 18.9-25.6 USD, and at secondary care hospitals were 6.0-12.7, 6.0-18.9, and 12.2-18.9 USD. Every $1 reimbursed at drug stores will save additional costs in Thailand's health system, ranging from $0.04 to $0.24 and $0.02 to $0.16 at tertiary care hospitals and secondary hospitals, respectively.Conclusion Pharmacy services for 16 common illness symptoms can clearly save costs.